2010
DOI: 10.1097/jto.0b013e3181e77604
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar Resection: A Movement from the Lung Cancer Study Group

Abstract: The 1995 Lung Cancer Study Group consensus recommending lobectomy for stage I non-small cell lung cancer (NSCLC) has directed lung cancer resections since its publication. However, enhancements in imaging technology over the last decade have produced larger cohorts of patients presenting with localized, early-stage disease. Today, multislice computer tomography is widely available, capable of detecting NSCLC at smaller sizes, with improved spatial resolution, and is used in screening programs for high-risk ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 75 publications
2
68
0
2
Order By: Relevance
“…However, some studies reported that survival after sublobar resection for small-sized (≤2 cm) NSCLC is similar to that of lobectomy (9). Further, randomized trials including lung cancer with solid features are currently ongoing to validate these conclusions (CALGB 140503, JCOG 0802) (10,11).…”
Section: Original Articlementioning
confidence: 99%
“…However, some studies reported that survival after sublobar resection for small-sized (≤2 cm) NSCLC is similar to that of lobectomy (9). Further, randomized trials including lung cancer with solid features are currently ongoing to validate these conclusions (CALGB 140503, JCOG 0802) (10,11).…”
Section: Original Articlementioning
confidence: 99%
“…Two recent reviews of sublobar resection concluded that wellselected use of sublobar resection, especially for pure AIS of f2 cm, yields comparable survival and recurrence rates to lobectomy [23,24]. In this way, sublobar resection is generally considered acceptable for GGO lesions or adenocarcinomas with minimal invasion.…”
Section: Sublobar (Limited) Resection For Lung Cancermentioning
confidence: 99%
“…19) The Cancer and Leukemia Group B (CALGB) 140503, phase III trial is ongoing to compare the recurrence-free survival of patients with a small tumor less than 2 cm in NSCLC undergoing lobectomy versus sublobar resection. 20) Also, the aim of this study is to compare the results of lobectomy by open thoracotomy to VATS or the results of sublobar resection by open thoracotomy to VATS. The results of this study will provide more precise and reliable information about the advantages or disadvantages of VATS segementectomy.…”
Section: Discussionmentioning
confidence: 99%